2010
DOI: 10.1089/end.2009.0407
|View full text |Cite
|
Sign up to set email alerts
|

Totally Ultrasound Versus Fluoroscopically Guided Complete Supine Percutaneous Nephrolithotripsy: A First Report

Abstract: We showed that totally ultrasound-guided complete supine PCNL is safe and feasible even in reoperative patients. It has certain advantages such as elimination of X-ray exposure to the surgeon and staff of the operating room, avoidance of contrast material administration, identification of all the tissue between the skin and kidney, and the energy expenditure of the surgeon and other staff of the operating room is decreased as it is not necessary to wear a lead shield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…Type I and II cases had calculi in the upper ureteral, UPJ, or pelvic calculi combined with middle/severe hydronephrosis. The calculi could be satisfactorily removed with X-ray or B ultrasound by puncturing the renal middle calyx at the 11th intercostal or the subcostal space [10][11][12]. Although this puncture operation is simple, the upper calyx calculi can be easily removed because the channel is established through the lower calyx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type I and II cases had calculi in the upper ureteral, UPJ, or pelvic calculi combined with middle/severe hydronephrosis. The calculi could be satisfactorily removed with X-ray or B ultrasound by puncturing the renal middle calyx at the 11th intercostal or the subcostal space [10][11][12]. Although this puncture operation is simple, the upper calyx calculi can be easily removed because the channel is established through the lower calyx.…”
Section: Discussionmentioning
confidence: 99%
“…Two or more channels in this type should be established conventionally to complete the operation, thereby resulting in the highest residual rate. The use of an ultrasonic lithotripter (EMS) can significantly improve the efficiency of stone extraction and reduce the residual stones as well as the number of the established channels [10,12,13]. (3) Perfusion pressure should be maintained at the lowest possible rate during operation, and the operation time should be strictly controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,38,39 Ultrasonography can be an appropriate alternative for fluoroscopy due to suitable outcomes, minimum radiation exposure, proper anatomical identification despite longer access and operative times, and the need for adequate skills or experience. 32,33,[38][39][40] In children, mid-calyceal puncture had a significant effect on complications.21 Shin and colleagues found that a punctured calyx did not predict grade ≥IIIa.6 Aron and colleagues reported similar complication rates for superior and inferior calyceal punctures in complex inferior calyceal stones. 41 In another study, middle and lower calices accesses had similar complication rates and MCC.…”
mentioning
confidence: 99%
“…Different studies demonstrated similar complications between ultrasonography and fluoroscopy, and imaging type had no significant effect on complication rates in children. 21,38,39 Ultrasonography can be an appropriate alternative for fluoroscopy due to suitable outcomes, minimum radiation exposure, proper anatomical identification despite longer access and operative times, and the need for adequate skills or experience. 32,33,[38][39][40] In children, mid-calyceal puncture had a significant effect on complications.…”
mentioning
confidence: 99%